Association of a Novel Nonsense Mutation in KIAA1279 with Goldberg-Shprintzen Syndrome - SALEHPOUR, Shadab; HASHEMI-GORJI, Feyzollah; SOLTANI, Ziba; GHAFOURI-FARD, Soudeh; MIRYOUNESI, Mohammad (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Salehpour Sh, Hashemi-Gorji F, Soltani Z, Ghafouri-Fard S, Miryounesi M. Association of a Novel Nonsense Mutation in KIAA1279 with Goldberg-Shprintzen Syndrome. Iran J Child Neurol. Winter 2017; 11(1):70-74. Abstract Goldberg-Shprintzen syndrome (OMIM 609460) (GOSHS) is an autosomal recessive multiple congenital anomaly syndrome distinguished by intellectual disability, microcephaly, and dysmorphic facial characteristics. Most affected individuals also have Hirschsprung disease and/or gyral abnormalities of the brain. This syndrome has been associated with KIAA1279 gene mutations at 10q22.1. Here we report a 16 yr old male patient referred to Center for Comprehensive Genetic Services, Tehran, Iran in 2015 with cardinal features of GOSHS in addition to refractory seizures. Whole exome sequencing in the patient revealed a novel nonsense (stop gain) homozygous mutation in KIAA1279 gene (KIAA1279: NM_015634:exon6:c.C976T:p.Q326X). Considering the wide range of phenotypic variations in GOSHS, relying on phenotypic characteristics for discrimination of GOSH from similar syndromes may lead to misdiagnosis. Consequently, molecular diagnostic tools would help in accurate diagnosis of such overlapping phenotypes. References 1. Goldberg R, Shprintzen R. Hirschsprung megacolon and cleft palate in two sibs. J Craniofac Genet Dev Biol 1980;1(2):185-9. 2. Yomo A, Taira T, Kondo I. Goldberg-Shprintzen syndrome: Hirschsprung disease, hypotonia, and ptosis in sibs. Am J Med Genet 1991;41(2):188-91. 3. Drevillon L, Megarbane A, Demeer B, Matar C, Benit P, Briand-Suleau A, et al. KBP-cytoskeleton interactions underlie developmental anomalies in Goldberg-Shprintzen syndrome. Hum Mol Genet 2013;22(12):2387-99. 4. Brooks AS, Bertoli-Avella AM, Burzynski GM, Breedveld GJ, Osinga J, Boven LG, et al. Homozygous nonsense mutations in KIAA1279 are associated with malformations of the central and enteric nervous systems. Am J Med Genet 2005;77(1):120-6. 5. Blatch GL, Lassle M. The tetratricopeptide repeat: a structural motif mediating protein-protein interactions. BioEssays 1999;21(11):932-9. 6. Alves MM, Burzynski G, Delalande J-M, Osinga J, van der Goot A, Dolga AM, et al. KBP interacts with SCG10, linking Goldberg–Shprintzen syndrome to microtubule dynamics and neuronal differentiation. Hum Mol Genet 2010:ddq280. 7. Valence S, Poirier K, Lebrun N, Saillour Y, Sonigo P, Bessières B, et al. Homozygous truncating mutation of the KBP gene, encoding a KIF1B-binding protein, in a familial case of fetal polymicrogyria. Neurogenetics 2013;14(3-4):215-24. 8. Murphy HR, Carver MJ, Brooks AS, Kenny SE, Ellis IH. Two brothers with Goldberg-Shprintzen syndrome. Clinl Dysmorphol 2006;15(3):165-9.